What's on the menu? Delivering evidence-based nutritional therapy. Issue 8 (August 2015) - McCarthy, Mary S.; Martindale, Robert G.
<x xml:space="preserve">Abstract</x> Review best practices in nutrition therapy, including recommendations for managing five of the top challenges nurses face when delivering enteral nutrition to acutely ill patients. Then incorporate the evidence into nursing practice so patients experience the benefits of optimal nutrition therapy, including shorter hospital stays and reduced mortality.